A BOOK REVIEW OF “MENTORING IN CONTEMPORARY EDUCATION” - Nadezhda Kaloyanova (Педагогически форум)
The book "Mentoring in Contemporary Education" by Margarita Slavova, PhD presents a comprehensive and in-depth experimental educational study aimed at validating a model for mentoring young newly appointed teachers in educational institutions. Regulations that have come into effect in recent years regulate the implementation of the described process in the educational system. In this sense, the researched issue of mentoring is very timely, relevant and must find the necessary place in the implementation of the reform in education in order to improve the adaptation of young teachers to the profession.